Hybrid electronic health records - Pedrosa, Tiago (2013)
The research related with digital health records has been a hot topic since the last two decades, producing diverse results, particularly in two main types – Electronic Health Records and Personal Health Records. With the current wider citizen mobility, the liberalization of health care providing, as well as alternative medicine, elderly care and remote patient monitoring, new challenges had emerged. These brought more actors to the scene that can belong to different healthcare networks, private or public sector even from different countries. For creating a true patient-centric electronic health record, those actors need to collaborate in the creation and maintenance of the record. In this work, the Hybrid Electronic Health Record (HEHR) is presented, describing how information can be created and used, as well as focusing on how the patient defines the access control. Some new services are also discussed.